Search for Third Generation Scalar Leptoquarks Decaying into tau b - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Amer Physical Soc, 2008)
We have searched for third generation leptoquarks (LQ(3)) using 1.05 fb(-1) of data collected with the D0 detector at the Fermilab Tevatron Collider operating at s=1.96 TeV. We set a 95% C.L. lower limit of 210 GeV on the mass of a scalar LQ(3) state decaying solely to a b quark and a tau lepton.